Identification Of Nonlinear Characteristic Of The Rubber Mount - Darun, Hasratul Azwan (Universiti Sains Malaysia, 2017)
Rubber mount is a type of vibration isolator. It provides an interface between two parts, damping the energy transmitted through the rubber mount. A common application is the engine mounting where the rubber mount is used to reduce vibration transmitted by the engine towards the passenger compartment. This paper investigates the nonlinear characteristic of the rubber mount using the hysteresis loop method. The test done in this paper is shaker test. The test setup consists of accelerometer, force transducer, shaker, power amplifier, LMS data acquisition system, impact hammer. The usage of LMS analyzer and LMS test lab ensured the data obtain is accurately recorded according to the test and the received signal. Shaker tests were performed to determine the nonlinear characteristics of the rubber mount which the range of operation is 3.0N to 10.0N for the amplitude of excitation and range of 0Hz to 300Hz for the excitation frequency. It was found out that the stiffness of the rubber mount decreases as the amplitude of excitation increases before achieving transition. The loss factor obtain from hysteresis loop increases as the amplitude of excitation increases before achieving transition. The rubber mount shows its nonlinear characteristic at the frequency of 80Hz with different amplitude of excitation ranging from 3.0N to 10.0N.